2012
DOI: 10.15376/biores.7.4.5247-5257
|View full text |Cite
|
Sign up to set email alerts
|

Ecf and TCF Bleaching of Saccharum Officinerum-Co89003 Bagasse Soda-Aq Pulp With Alkali-Thermo-Tolerant Crude Xylanase From Coprinellus Disseminatus Sw-1 Ntcc1165

Abstract: An alkali-thermo-tolerant crude xylanase from Coprinellus disseminatus SW-1 NTCC1165 produced under solid-state fermentation conditions improves the brightness of sugarcane bagasse soda-AQ pulp by 7.3, 4.7, 6.1, and 8.2% in XODED, XOD(E OP )DP, OX(E OP )P, and XO(E OP )P bleaching sequences, respectively, at an enzyme dose of 8IU/g, a reaction time of 120 min, a consistency of 10%, and a pH of 6.4 at 55 o C. An improvement in brightness by 2.1% for pulp bleached by XO(E OP )P compared to OX(E OP )P sequence va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Around 60% to 70% of bagasse mass is composed of useful fibers. The remaining mass is represented by non-fibrous parenchyma cells (pith) and soluble matter (Agnihotri et al 2010;Lois-Correa 2012). Due to its high content of pith, bagasse has high dewatering resistance and poor paper properties (Rainey 2012).…”
Section: Non-wood Pulpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 60% to 70% of bagasse mass is composed of useful fibers. The remaining mass is represented by non-fibrous parenchyma cells (pith) and soluble matter (Agnihotri et al 2010;Lois-Correa 2012). Due to its high content of pith, bagasse has high dewatering resistance and poor paper properties (Rainey 2012).…”
Section: Non-wood Pulpsmentioning
confidence: 99%
“…The high quantity of ashes cannot be considered so problematic since the silica-based salts are negligible. High hemicellulose content benefits the paper strength (Agnihotri et al 2010).…”
Section: Non-wood Pulpsmentioning
confidence: 99%
“…The pulp also showed an improvement in brightness due to selective delignification. The xylan removal enhanced the degree of external fibrillation on fiber surface, which improved the tear index after xylanase pretreatment of bagasse pulp (Agnihotri et al 2012). Zou et al (2002) demonstrated that hemicelluloses, specifically xylan, could act as protective factors against cellulose degradation.…”
Section: Effect Of Mechanical and Xylanase Pretreatment On Strength Propertiesmentioning
confidence: 99%
“…These include non-woody plants such as C. sativa, I. carnea (Dutt and Tyagi 2010), H. cannabinus, H. sabdariffa (Upadhyaya et al 2008), S. aculeata, and S. sesban (Dutt et al 2004(Dutt et al , 2005. Agricultural residues including sugarcane bagasse and wheat straw (Agnihotri et al 2010;Singh et al 2011), fast-growing hardwoods such as C. equisetifolia (Maan et al 2018) and L. leucocephala (Poonam and Dutt 2014;Maan and Dutt 2017), and waste papers have also been investigated. L. leucocephala and C. equisetifolia are two fast-growing hardwoods that belong to the families of Fabaceae and Casuarinaceae, respectively.…”
Section: Introductionmentioning
confidence: 99%